CARBON ISOTOPIC COMPOSITIONS OF PROKARYOTIC LIPIDS AS TRACERS OF CARBON CYCLING IN DIVERSE SETTINGS - Pancost R.D.; Sinninghe Damsté J.S. (My University, 2003)
Recent work has highlighted the ubiquity of bacteria and archaea and continues to affirm their significance in diverse biogeochemical processes. The δ13C values and distributions of diagnostic lipids derived from such microorganisms can provide insights into prokaryotic processes in modern settings and are one of the few means by which past prokaryotic processes in depositional settings can be elucidated. Here we present a brief review of prokaryotic lipids commonly observed in sediments and the controls on their carbon isotopic compositions. We then present two case studies—one of Mediterranean cold seeps at which anaerobic oxidation of methane occurs and one of a Holocene peat deposit in which a variety of aerobic and anaerobic microorganisms govern the degradation of organic matter. These two studies illustrate the potential utility of compound-specific carbon isotope analyses to deconvolute pathways of carbon flow in microbial communities.
Keywords: Bacteria; Archaea; Carbon isotopes; Peat; Cold seeps; Biomarkers; Hopanoids; Fatty acids; Ether lipids; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен